Assessing the effect of oxygen and microbial inhibitors to optimize ferricyanide-mediated BOD assay - Bonetto, Maria Celina (2011)
Methods for short-term BOD analysis (BODst) based on ferricyanide mediator reduction have succeeded in overcoming some problems associated with the standard BOD test analysis (BOD5) such as long-term incubations (5 days), the need to dilute samples and low reproducibility. Here we present a bioassay where a Klebsiella pneumoniae environmental strain successfully reduces ferricyanide without de-aeration of the samples with linear BOD5 ranges between 30 and 500 mg L -1 or 30 and 200 mg L-1, using glucose-glutamic acid solution (GGA) or OECD standards respectively. We further propose a new assay termination solution that allows higher reproducibility and standardization of the cell-based assay, employing formaldehyde (22.7 g L-1) or other compounds in order to stop ferricyanide reduction without affecting the amperometric detection and therefore replace the centrifugation step normally used to stop microbial-driven reactions in ferricyanide-mediated bioassays. These improvements led to an accurate determination of real municipal wastewater samples. © 2011 Elsevier B.V. All rights reserved.